Comparison of Alloderm and mucosal graft in mandibular vestibuloplasty - Mahmoodhashemi H.; Ghafari Gorakani S.; Akhondi N. (Tehran University of Medical Sciences, 2009)
"nBackground and Aim: The usage of free gingival grafts for vestibuloplasty is a routine procedure. The free gingival procedure requires harvesting the graft from a donor site which increases morbidity and the risk of surgical complications. In addition, adequate amount of donor tissue may not be available. Acceptable results of Alloderm application as a substitute for autogenous soft tissue grafts are: Not exposing the patient to an additional surgery, no donor site morbidity, unlimited availability, decreasing the bleeding during the surgery, decreasing the surgical complications, and better color match. The aim of this study was to evaluate the maintenance of the vestibular depth in vestibuloplasty with mucosal graft and Alloderm."nMaterials and Methods: Both methods of anterior mandibular vestibuloplasty by Clark, utilizing Alloderm and mucosal grafts, were employed in ten clinical cases. During the surgeries, half the prepared recipient sites received Alloderm, while the remaining half received autografts in a randomized fashion. Immediately, 1, 3, and 6 months postoperatively, the variables of graft rejection, depth of vestibule and the degree of relapse were evaluated. SPSS software was used for analysis of the data and the methods used for "statistical tests" were as follows: Friedman Method, Paired sample t-test, Smirnov-kolmogrove Method. (The statistical significance level was established at P-value<0.05."nResults: The mean difference of the relapse measurements in both methods throughout the survey did not have significant predictive value (P>0.05). Similar results were achieved for the mean difference of depth of the vestibule."nConclusion: In patients undergoing Vestibuloplasty, Alloderm could be material of choice to be utilized as autogenic soft tissue grafts in pre-prosthesis procedures.